The Detrimental Effects of Oral Bad Habits on Children's Oral Health and Dental Development - Irawan, Aulia; Marsyama’ah (Phlox Institute: Indonesian Medical Research Organization, 2023)
Oral bad habits refer to external sources, such as nail biting, item biting (e.g., pencils and pens), finger sucking, cheek sucking, and mouth breathing. The act of inhaling and exhaling through the mouth is the predominant behavior that frequently leads to irregularities in the facial composition and misalignment of the teeth. Mouth breathing during the growth and development phase can impact dentocraniofacial growth. Persistent mouth breathing results in muscular anomalies in the vicinity of the mouth, perhaps resulting in malocclusion. The purpose of this review is to delineate detrimental oral behaviors in children and elucidate their repercussions on oral health and dental development.